2022
DOI: 10.1111/1556-4029.15019
|View full text |Cite
|
Sign up to set email alerts
|

Validating strength‐of‐support conclusion scales for fingerprint, footwear, and toolmark impressions

Abstract: In the pattern comparison disciplines such as fingerprints, footwear, and toolmarks, the results of a comparison are communicated by examiners in the form of categorical conclusions such as Identification or Exclusion. These statements have been criticized as requiring knowledge of prior probabilities by the examiners and being overinterpreted by laypersons. Alternative statements based on strength‐of‐support language have been proposed. The current study compares traditional conclusion scales against strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The participants in this study were directed to use the AFTE range of conclusions [ 46 ], which predominates in North America, to express their comparison decisions. Alternative scales, which describe conclusions in terms of strength of support, are under consideration [ 59 , 60 ]. If adopted by the community, the value of studies using the AFTE range will endure.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in this study were directed to use the AFTE range of conclusions [ 46 ], which predominates in North America, to express their comparison decisions. Alternative scales, which describe conclusions in terms of strength of support, are under consideration [ 59 , 60 ]. If adopted by the community, the value of studies using the AFTE range will endure.…”
Section: Discussionmentioning
confidence: 99%
“…They completed all four tasks (described below; three visual comparison tasks and one divergent validity task) in a randomised order and completed all trials in each task in a randomised order (except for the HMT‐SF which participants completed in its set order). We selected artificial‐print comparison from the Novel Object‐Matching Test as the most predictive task of visual comparison performance (as in Growns et al, 2022) and two novel tasks adapted from Busey et al (2022): footwear and toolmark comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed 56 toolmark comparison trials (28 match and 28 non-match) from Busey et al (2022; see middle panel of Figure 1).…”
Section: Toolmark Comparisonmentioning
confidence: 99%
“…According to them, the strengths of expanded conclusion scales outweigh the limitations, but care must be taken with their implementation. A further study contrasted fingerprint, toolmarks and footwear marks [ 100 ]. It confirmed that examiners become more risk-averse with expanded scales (both on the source identification and source exclusion) and conclusion statements that contains “extremely strong support” are reserved for comparisons with the highest amount of support.…”
Section: Friction Ridge Skin and Its Individualization Processmentioning
confidence: 99%